2018
DOI: 10.4314/ejhs.v28i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Severe Head Injury and Its Associated Factors among Head Injury Patients in Gedeo Zone, Southern Ethiopia: A Two-Year Retrospective Study

Abstract: BackgroundSevere head injury is a major public health threat that is the main cause of morbidity and mortality in all age groups of the world's populations including Ethiopia. In view of this, this study was assessed the severity of head injury and its contributing factors.MethodsA Two-year retrospective study was conducted at Dilla University Referral Hospital, from December 2014 to November 2016. All head injury patients admitted to the surgical ward were included. Bivariate and multivariate regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Deaths are positively correlated with severe head injuries in all age groups. Head injury was mild in the majority of head injury victims, followed by severe and moderate based on the Glasgow Coma Scale (GCS) score [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deaths are positively correlated with severe head injuries in all age groups. Head injury was mild in the majority of head injury victims, followed by severe and moderate based on the Glasgow Coma Scale (GCS) score [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to other studies in most of the literatures' mentioned. 7,8,[10][11][12][13] This difference is related to different factors like involvement the young population in risky recreational activities like alcohol consumption. Males also have high risk activities especially in trying to achieve economic stability.…”
Section: Discussionmentioning
confidence: 99%
“…Jimma and Dilla) and other countries, road traffic accident is major cause of head injury. 7,8,13 This tells that we need to work more in creating awareness and reinforcing implementation of driving rules and regulations. Private and public transportation were main means of delivering patients to hospital, which is similar to studies done in Africa but literatures from developed countries show ambulance is main transportation and this has changed the outcome of head injury patients significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted at Ayder Referral Hospital shows the prevalence of head injury from a review of records of road traffic accident was 48.7% (16). Another study conducted at Dilla University referral hospital shows the prevalence of head injury was 32.1%, and road traffic accident was the main cause of head injury (17). A study at Gondar University referral hospital also showed a prevalence of 40.5% for head injury; of these 46.7% occurred due to interpersonal fight (18).…”
Section: Introductionmentioning
confidence: 99%